Clinical Effect and Rotational Stability of TICL in the Treatment of Myopic Astigmatism - Manhui Zhu; Linling Zhu; Qiujian Zhu; Cailian Xu; Peng Yu; Haiyang Xiao; Ying Wang; You Yuan (Journal of Ophthalmology)
Purpose. To investigate the clinical outcomes and possible risk factors associated with rotational stability after the implantation of a V4c toric implantable Collamer lens (TICL) for the correction of moderate to high myopic astigmatism. Methods. A total of 112 eyes of 66 patients with moderate to high myopic astigmatism underwent TICL implantation. All patients were followed up for more than 1 year. The uncorrected and best-corrected visual acuity (UCVA and BCVA), astigmatism and spherical equivalent, intraocular pressure, vault, endothelial cell morphometry, and rotation of the TICL axis were assessed at l day, 1 week, 1 month, 3 months, 6 months, and 12 months postoperatively. Postoperative rotation was defined as the angle between the intended axis and the achieved axis. Regression analysis was used to investigate the possible risk factors for TICL rotation postoperatively. Results. The mean efficacy index and safety index 12 months postoperatively were 1.03 ± 0.09 and 1.05 ± 0.10, respectively. All patients had the same or better visual acuity than preoperatively. The mean astigmatism value decreased from −1.86 ± 0.79 D preoperatively to −0.37 ± 0.35 D. The mean absolute axis deviation of the TICL at the last follow-up was 2.75 ± 2.04° (range, 0°∼11°). The mean manifest refraction spherical equivalent (MRSE) changed from -9.04 ± 2.67 D preoperatively to −0.67 ± 0.51 D postoperatively. The logistic regression demonstrated that the absolute degree of TICL rotation had a significant association with the fixation angle of the TICL and the size of the lens (P=0.003, P=0.026, resp.). Conclusion. The results of our study support that TICL implantation is safe, effective, and predictable in the treatment of moderate to high myopic astigmatism, with relatively good postoperative rotational stability.